LEASURE TIME ACTIVITY AMONG STUDENTS FROM UNIVERSITY OF PRISHTINA, FAKULTY OF PHYSICAL EDUCATION AND SPORT - Besnik Morina; Shemsedin Vehapi; Bahri Gjinovci; Besim Halilaj; Ilir Gllareva; Malsor Gjonbalaj; Leon Dukaj (Sport Mont, 2015)
This paper presents the results of the research on the physical activity of students in the Faculty of Physical Education and Sport, University of Prishtina “Hasan Prishtina” Kosovo. The purpose of this cognitive study was to diagnose certain aspects of the lifestyle of students, with a particular focus on physical activity and, the difference in sex. The practical aim, however, was an indication of such actions, arising from past experience that would aim at improving lifestyle, and could lead to the elimination or prevention of certain causes of not making movement activity by the students in our country. The research was conducted by the use of diagnostic survey in the group of 120 people aged 18-37, among whom there were 56 girls and 64 boys. The research material was collected in 2014. The research that was carried out shows that the level of wealth (not so much of the family, but of the whole country) may have an impact on the choice of activities taken by the students. Undoubtedly socio-cultural factors and the tradition of social life, which impose certain ways of spending leisure time (particularly in the case of the students) as we can see in the results obtained, where we also found that there is no statistically significant differences between girls and boys. The above observations, taking into account local conditions, should be the starting point for all those who plan introducing changes in physical education systems in my country in the future.